# math

posted by
**Leo** on
.

2.)If f(x)=3x,g(x)=x-3,and h(x)= the square root of x, find (fogox)(X). I really didn't get this will someone please show me how to do it?

This I what I did to solve for it:

3(x-3)

3(he square root of 25-3

3(5-3)

15-9=6

Ok here is another way I solved for it but I am still not sure if I am doing any of the work right.

f(g(h))(25)

f(g(square root of f(x)))(25)

f(g(1.7))(25)

f(1.7-3)

F(-1.3)

f(25)=3(25)

f(25)=75

Which one is correct and if they are both wrong will you help me get the right answer and understand how to do it?